Productivity, Growth and Labour Market Dynamics in Italy (1960-2023) - Angelone, Paolo; Canale, Rosaria Rita; Ferreiro, Jesus (Panoeconomicus, 2025)
This article aims to examine the evolution of the Italian economy from the 1960s to the present focusing on wage and labour productivity dynamics. Throughout this period, the issue of containing labour costs emerged. On one hand, it provided a competitive advantage, but on the other exerted downward pressure on employment, aggregate demand, productivity, and economic growth. These contradictions and vulnerabilities began to emerge clearly since the 1980s with the intensification of the processes of economic tertiarization, international market integration and a general reduction in workers' bargaining power, further aggravated by the lack of policy manoeuvrability due to European constraints and austerity. Within a context characterized by small businesses, factors such as outsourcing, the adoption of a two-tier bargaining system, and increasing labour flexibility have been discouraging investments and productivity, thus locking Italy into a development model that risks further decline. JEL: E02, E24, N34, O40.